Analisis Faktor-Faktor Sosial Ekonomi yang Berpengaruh Terhadap Pendapatan Usaha Industri Gula Aren di Kecamatan Selupu Rejang - Mira Yanuarti; Cikit Apriyanti; Dwita Prisdinawati; Putri Milanda B (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2023)
The purpose of this study was to determine the effect of variables on the level of formal education and the level of non-formal education on the income of palm sugar craftsmen in Selupu Rejang District, Rejang Lebong Regency. This research was conducted in January 2022 located in Selupu Rejang District. Determination of respondents in this study using the slovin method. The data analysis used is multiple linear regression analysis using a dummy variable, namely the level of non-formal education that has been attended by palm sugar craftsmen, both government and non-government institutions. The results of this study obtained the equation Y = 28.257 + 0.211X1 + 3.388Di + e with the results of the analysis that the results of the t test calculated the level of non-formal education had a significant effect on the income of palm sugar craftsmen with a tcount of 2.069 greater than the ttable value of 0.683.